New possibility of the latent disease detection in students using the screening method in programme «health»: introduction and efficacy - S S Vyalov; V I Kuznetzov; A M Khodorovich (RUDN Journal of Medicine, 2010)
The new method of the latent chronic disease detection in students using the screening was invented in programme «Health». It was research in students from the different climatogeographic regions for the detection of gastrointestinal disease. The special screening questionnaire designed by us was used in the study. The perceptibility and the diagnostic specificity was studied and estimated. The efficacy of screening use for gastrointestinal disease early diagnostic was ascertained as a result of study. It was marked the significant spread of intestinal dysbacteriosis in students form different climatogeographic regions in adaptation period.